Clinical Outcomes of Laser Peripheral Iridotomy in Eyes with Primary Angle Closure Suspect and Primary Angle Closure - Faresa Hilda; Astrianda Suryono; Widya Artini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Primary angle closure glaucoma (PACG) is a leading cause of bilateral blindness worldwide. Laser peripheral iridotomy (LPI) has been proposed as the standard prophylactic option for patients with the risk of developing the spectrum of disease, from primary angle closure suspect (PACS) toprimary angle closure (PAC) then to PACG. We aim to evaluate the effect of LPI on intraocular pressure(IOP), anterior chamber depth (ACD) and angle width, as prophylactic management in PACS and PAC.Methods: Literature search was conducted from MEDLINE database using Pubmed search engine.Inclusion criteria were all studies (interventional and observational) that reported outcomes of LPI onPACS and/or PAC eyes. Exclusion criteria were outcomes of LPI on PACG eyes.Results: There were 8 studies included in this literature review; 4 studies evaluated patients with PACS,1 study evaluated patients with PAC, while 3 studies had compared between PACS and PAC. FollowingLPI, majority of the studies showed a decrease of IOP when compared to baseline. While, 5 studiesevaluated changes of central ACD and majority of those studies indicated deepening of ACD. Fourstudies had assessed the angle width changes after LPI that revealed advancement of angle width.Conclusion: The results of this literature review showed that LPI in PACS and PAC eyes showed decrease of IOP within a specified period, the deepening of central ACD and increase of angle width.Keywords: Primary angle closure suspect, primary angle closure, laser peripheral iridotomy